2003
DOI: 10.1161/01.res.0000070111.98158.6c
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Is Constitutively Expressed on Platelets and Provides a Novel Mechanism for Platelet Activation

Abstract: Abstract-CD40 is a 48-kDa phosphorylated transmembrane glycoprotein belonging to the TNF receptor superfamily.CD40 has been demonstrated on a range of cell types, and it has an important role in adaptive immunity and inflammation. CD40 has recently been described on platelets but platelet activation by CD40 has not been described.In the present study, we use flow cytometry and immunoblotting to confirm that platelets constitutively express surface CD40. CD40 mRNA was undetectable, suggesting that the protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
261
6
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(284 citation statements)
references
References 44 publications
13
261
6
4
Order By: Relevance
“…We have previously shown that activated platelets bind to leukocytes and can be detected as platelet monocyte aggregates (PMA) (30). Levels of activated PMA were higher in the ACS group than in the SA group in both the CO (p=0.0003) and RA (p=0.04) Figure 5.…”
Section: Platelet Activation Is a Feature Of Acsmentioning
confidence: 91%
“…We have previously shown that activated platelets bind to leukocytes and can be detected as platelet monocyte aggregates (PMA) (30). Levels of activated PMA were higher in the ACS group than in the SA group in both the CO (p=0.0003) and RA (p=0.04) Figure 5.…”
Section: Platelet Activation Is a Feature Of Acsmentioning
confidence: 91%
“…Furthermore, CD40 has recently been shown to be constitutively expressed on the surface of platelets and that its ligation results in platelet activation, which may serve to further enhance platelet-driven thrombus formation. 63 Finally, CD40L inhibits EC migration. 58 By preventing ECs to migrate, reendothelialization of any plaque erosions is impaired, enhancing the possibility of an acute atherosclerotic event.…”
Section: Szmitko Et Al Inflammation and Endothelial Cell Activationmentioning
confidence: 99%
“…When platelets are activated, CD40L moves from intracellular sites to the platelet surface (1,3,4). Membrane CD40L may then be cleaved, producing a soluble trimeric fragment known as sCD40L.…”
Section: Abstract Platelets; Platelet Activation; Pediatric; Referencmentioning
confidence: 99%
“…(3,8,9). CD40L also plays a role in thrombosis by inducing TF expression on endothelial cells and monocytes, operating as a platelet agonist, and stabilizing arterial thrombi (1,3,8,10). Notably, these functions are not mediated exclusively via CD40L-CD40 interactions, because the integrin receptors αIIb βIII and α5β1 have also been found to bind CD40L (10,11).…”
Section: Abstract Platelets; Platelet Activation; Pediatric; Referencmentioning
confidence: 99%
See 1 more Smart Citation